Guardianship for crime prevention: a critical review of the literature - Hollis-Peel, Meghan E. (Crime, law and social change, 2011)
Cohen and Felson’s (Cohen and Felson American Sociological Review 44(4):588-608, 1979) routine activity theory posits that for a crime to occur three necessary elements must converge in time and space: motivated offenders, suitable targets, and the absence of capable guardianship. Capable guardians can serve as a key actor in the crime event model; one who can disrupt, either directly or indirectly, the interaction between a motivated offender and a suitable target. This article critically reviews the literature on guardianship for crime prevention. Our specific focus is two-fold: (1) to review the way guardianship has been operationalized and measured, and (2) to review experimental and quasi-experimental evaluations and field tests of guardianship. Research on routine activities has had an uneven focus resulting in the neglect of the guardianship component (Reynald Crime Prevention and Community Safety 11(1):1-20, 2009; Sampson et al. Security Journal 23(1):37-51, 2010; Tewksbury and Mustaine Criminal Justice and Behavior 30(3):302-327, 2003; Wilcox et al. Criminology 45(4):771-803 2007). Evaluations of guardianship-related interventions demonstrate support for the theoretical construct; however, high-quality field tests of guardianship are wholly lacking. Implications for theory and research are discussed.